Technology, utilization and inflation: what drives the New Keynesian Phillips Curve? - Peter McAdam; Alpo Willman (European Central Bank (ECB), 2011)
We argue that the New-Keynesian Phillips Curve literature has failed to deliver a convincing measure of “fundamental inflation”. We start from a careful modeling of optimal price setting allowing for non-unitary factor substitution, non-neutral technical change and timevarying factor utilization rates. This ensures the resulting real marginal cost measures match volatility reductions and level changes witnessed in many US time series. The cost measure comprises conventional counter-cyclical cost elements plus pro-cyclical (and co-varying) utilization rates. Although pro-cyclical elements dominate, real marginal costs are becoming less cyclical over time. Incorporating this richer driving variable produces more plausible price-stickiness estimates than otherwise and suggests a more balanced weight of backward and forward-looking inflation expectations than commonly found. Our results challenge existing views of inflation determinants and have important implications for modeling inflation in New-Keynesian models.
Keywords: E20; E30; 330; cyclicality; inflation; intensive labor; Labor Share; overtime premia; production function; real marginal costs; utilization